Fc or not Fc; that is the question: Antibody Fc-receptor interactions are key to universal influenza vaccine design. Issue 6 (3rd June 2017) - Jegaskanda, Sinthujan; Vanderven, Hillary A.; Wheatley, Adam K.; Kent, Stephen J.
ABSTRACT: A universal vaccine that provides long-lasting protection from both epidemic and pandemic influenza viruses remains the "holy grail" of influenza vaccine research. Though virus neutralization assays are the current benchmark of measuring vaccine effectiveness, it is clear that Fc-receptor functions can drastically improve the effectiveness of antibodies and vaccines in vivo . Antibodies that kill virus-infected cells and/or elicit an antiviral environment, termed antibody-dependent cellular cytotoxicity (ADCC)-mediating antibodies, provide a link between the innate and adaptive immune response. New technologies allowing the rapid isolation and characterization of monoclonal antibodies (mAb) have yielded a plethora of mAbs which target conserved regions of influenza virus, such as the hemagglutinin (HA) stem region. Many such mAbs have been used to gain a better understanding of Fc-receptor functions in vivo . In parallel, several studies have characterized the induction of polyclonal ADCC following influenza vaccination and infection in humans. Taken together, these studies suggest that ADCC-mediating antibodies (ADCC-Abs) significantly contribute to host immunity against influenza virus and may be a mechanism to exploit for rational vaccine and therapeutic design. We discuss recent research on influenza-specific ADCC and potential future avenues to extend our understanding.